Analysis of Interface Sliding in a Composite I-Steel–Concrete Beam Reinforced by a Composite Material Plate: The Effect of Concrete–Steel Connection Modes - Daouadji, Tahar Hassaine; Abbès, Boussad; Bensatallah, Tayeb; Abbès, Fazilay (Journal of Composites Science, 2025)
This study investigates interface sliding behavior in composite I-steel–concrete beams reinforced with a composite material plate by analyzing various connection configurations combining shear stud connectors and adhesive bonding. The degree of composite action, governed by the shear stiffness at the steel–concrete interface, plays a critical role in structural performance. An analytical model was developed based on the elasticity theory and the strain compatibility approach, assuming constant shear and normal stress across the interface. Five connection modes were considered, ranging from fully mechanical (100% shear studs) to fully adhesive (100% bonding), as well as mixed configurations. The model was validated against finite element simulations, demonstrating strong agreement with relative differences between 0.3% and 10.7% across all cases. A parametric study explored the influence of key factors such as interface layer stiffness and composite plate reinforcement material on the overall interface behavior. The results showed that adhesive bonding significantly reduces slippage at the steel–concrete interface, enhancing bond integrity, while purely mechanical connections tend to increase interface slippage. The findings provide valuable guidance for designing hybrid connection systems in composite structures to optimize performance, durability, and construction efficiency.
Number: 6
Keywords: adhesive bonding; analytical analysis; finite-element analysis; interfacial slip; interfacial stresses; shear deformations; steel–concrete composite beam